The unwanted child: the fate of foundlings, orphans, and juvenile criminals in early modern Germany - Harrington, Joel F. (Univ. of Chicago Press, 2009)
The unmarried mother -- The absconding father -- The beleaguered magistrate -- The street orphan -- The state wards -- From micro- to macro-: individuals and the big picture -- Appendix 1. The Findelkinder Database -- Appendix 2. Known infanticides in Nuremberg, 1384-1806